The effect of variable doses of inorganic nitrate-rich beetroot juice on simulated 2000-m rowing performance in trained athletes - Hoon, M. W.; Jones, A. M.; Johnson, N. A.; Blackwell, J. R.; Broad, E. M.; Lundy, B.; Rice, A. J.; Burke, L. M. (International Journal of Sports Physiology and Performance, 2014)
Context: Beetroot juice is a naturally rich source of inorganic nitrate (NO3-), a compound hypothesized to enhance endurance performance by improving exercise efficiency. Purpose: To investigate the effect of different doses of beetroot juice on 2000-m ergometer-rowing performance in highly trained athletes. Methods: Ten highly trained male rowers volunteered to participate in a placebo-controlled, double-blinded crossover study. Two hours before undertaking a 2000-m rowing-ergometer test, subjects consumed beetroot juice containing 0 mmol (placebo), 4.2 mmol (SINGLE), or 8.4 mmol (DOUBLE) NO3-. Blood samples were taken before supplement ingestion and immediately before the rowing test for analysis of plasma [NO3-] and [nitrite (NO2-)]. Results: The SINGLE dose demonstrated a trivial effect on time to complete 2000 m compared with placebo (mean difference: 0.2 ± 2.5 s). A possibly beneficial effect was found with DOUBLE compared with SINGLE (mean difference -1.8 ± 2.1 s) and with placebo (-1.6 ± 1.6 s). Plasma [NO2-] and [NO3-] demonstrated a dose-response effect, with greater amounts of ingested nitrate leading to substantially higher concentrations (DOUBLE > SINGLE > placebo). There was a moderate but insignificant correlation (r = -.593, P = .055) between change in plasma [NO2-] and performance time. Conclusion: Compared with nitratedepleted beetroot juice, a high (8.4 mmol NO3-) but not moderate (4.2 mmol NO3-) dose of NO3- in beetroot juice, consumed 2 h before exercise, may improve 2000-m rowing performance in highly trained athletes.